2001
DOI: 10.1111/j.0006-341x.2001.00126.x
|View full text |Cite
|
Sign up to set email alerts
|

A Covariance Estimator for GEE with Improved Small‐Sample Properties

Abstract: In this paper, we propose an alternative covariance estimator to the robust covariance estimator of generalized estimating equations (GEE). Hypothesis tests using the robust covariance estimator can have inflated size when the number of independent clusters is small. Resampling methods, such as the jackknife and bootstrap, have been suggested for covariance estimation when the number of clusters is small. A drawback of the resampling methods when the response is binary is that the methods can break down when t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
722
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 459 publications
(741 citation statements)
references
References 20 publications
19
722
0
Order By: Relevance
“…Due to the fact that the fitted value μ̂i tends to be closer to Y i than the true value μ i and when sample size is small, in V LZ is biased downward for estimating , and the bias turns to be larger when the sample is much smaller; meanwhile, a greater variability may arise [16,22]. Therefore, the hypothesis testing using V LZ tends to be liberal, and the resulting confidence interval is narrow.…”
Section: Modified Variance Estimators Of Gee With Small Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the fact that the fitted value μ̂i tends to be closer to Y i than the true value μ i and when sample size is small, in V LZ is biased downward for estimating , and the bias turns to be larger when the sample is much smaller; meanwhile, a greater variability may arise [16,22]. Therefore, the hypothesis testing using V LZ tends to be liberal, and the resulting confidence interval is narrow.…”
Section: Modified Variance Estimators Of Gee With Small Samplesmentioning
confidence: 99%
“…V MD is another bias-corrected "sandwich" variance estimator proposed by Mancl and DeRouen [22]. Unlike V KC , this estimator does not assume a correctly specified correlation structure, and it is written by (12) with (13) where I i and H ii are defined as the same as V KC .…”
Section: Modified Variance Estimators Of Gee With Small Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…This bias can be removed by dividing the squared error by the diagonal of the 'hat' matrix. It has also been found that using a t-distribution (or a Satterthwaite type degrees of freedom correction) and a jack-knife improves the estimate of the standard error [45][46][47]. Pan and Wall [47] proposed replacing the GEE Wald test by approximate t-or F-tests.…”
Section: Fitting Models To Datamentioning
confidence: 99%
“…They state that the GEE approach is asymptotically equivalent to the summary measure approach, and quote Mancl and De Rouen [46] to the effect that using bias-corrected variances can yield valid test sizes even with unequal cluster sizes and with as few as 10 clusters.…”
mentioning
confidence: 99%